Palynological Study of Kolosh Formation (Paleocene–Early Eocene), in Dokan area, Sulaimani, Kurdistan Region- Iraq - Srood Farooq Naqshabandi (Tikrit Journal of Pure Science, 2018)
The Kolosh Formation is belongs to Paleocene –Early Eocene cycle, this cycle is characterize by a complete development in the basin of deposition in all parts of Iraq.